2022
DOI: 10.3390/jcm11195928
|View full text |Cite
|
Sign up to set email alerts
|

Use of Human Albumin Administration for the Prevention and Treatment of Hyponatremia in Patients with Liver Cirrhosis: A Systematic Review and Meta-Analysis

Abstract: Background. Hyponatremia is a common complication of liver cirrhosis and aggravates patients’ outcomes. It may be corrected by human albumin (HA) infusion. Herein, we have conducted a systematic review and meta-analysis to evaluate the efficacy of intravenous HA administration for the prevention and treatment of hyponatremia in liver cirrhosis. Methods. Literature was searched in the PubMed, EMBASE, and Cochrane Library databases. If possible, a meta-analysis would be conducted. Incidence of hyponatremia, rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…111 Most previous studies have evaluated the role that albumin replacement plays in preventing hyponatremia after largevolume paracentesis in cirrhosis hyponatremia, but relatively few studies have evaluated the role that albumin plays in hyponatremia treatment. [112][113][114][115][116][117] In a retrospective multicenter study of 1,125 patients with liver cirrhosis accompanied by hyponatremia (regardless of large-volume paracentesis) at the time of admission, the delta values of the sNa concentrations between the albumin replacement group and the nonalbumin replacement group were compared, showing significantly higher delta values in the albumin replacement group. 113 In addition, the post-hoc analysis of the ANSWER study, which compared the group receiving long-term albumin treatment (20% human albumin in a 50 mL vial: 40 g twice a week for 2 weeks, then 40 g weekly thereafter) to the group receiving standard medical treatment, showed at the 3-month follow-up that albumin was associated with sNa normalization over time.…”
Section: Albuminmentioning
confidence: 99%
See 1 more Smart Citation
“…111 Most previous studies have evaluated the role that albumin replacement plays in preventing hyponatremia after largevolume paracentesis in cirrhosis hyponatremia, but relatively few studies have evaluated the role that albumin plays in hyponatremia treatment. [112][113][114][115][116][117] In a retrospective multicenter study of 1,125 patients with liver cirrhosis accompanied by hyponatremia (regardless of large-volume paracentesis) at the time of admission, the delta values of the sNa concentrations between the albumin replacement group and the nonalbumin replacement group were compared, showing significantly higher delta values in the albumin replacement group. 113 In addition, the post-hoc analysis of the ANSWER study, which compared the group receiving long-term albumin treatment (20% human albumin in a 50 mL vial: 40 g twice a week for 2 weeks, then 40 g weekly thereafter) to the group receiving standard medical treatment, showed at the 3-month follow-up that albumin was associated with sNa normalization over time.…”
Section: Albuminmentioning
confidence: 99%
“…115 The most recent meta-analysis evaluating the efficacy of albumin replacement also suggested that albumin replacement can be helpful in the prevention and treatment of hyponatremia in liver cirrhosis. 116 However, recommendations on the use of albumin replacement therapy in the management of cirrhosis with hyponatremia vary according to clinical guideline. While some suggest that albumin should be used to prevent or treat hyponatremia in liver cirrhosis, 103 other reports recommend that albumin infusions be carefully evaluated due to lack of data.…”
Section: Albuminmentioning
confidence: 99%
“…Although data regarding the use of albumin for hyponatremia in patients with cirrhosis are limited, multiple retrospective studies have demonstrated a possible mortality benefit. [43][44][45] Thus, albumin infusion should be considered in conjunction with fluid restriction for severe hyponatremia [5] and may also be considered for moderate hyponatremia.…”
Section: Intervention: Albuminmentioning
confidence: 99%
“…Most of them focus only on patients with decompensated liver cirrhosis, [5][6][7] or a single type of complication such as SBP, 8 HRS, 9 HE, 10,11 ascites, 12,13 infections, 14 or hyponatremia. 15 A review by Bai et al examined in 2022 the efficacy of human albumin infusion in cirrhotic patients, but it did not differentiate by comparators, in the main analysis it assessed all types of indications together and analysed only a few outcomes. 16 As for the potential benefit of long-term administration of albumin in patients with decompensated cirrhosis, mortality results in RCTs are discrepant.…”
Section: Introductionmentioning
confidence: 99%
“…Some reviews have been published analysing the efficacy of albumin administration in cirrhotic patients. Most of them focus only on patients with decompensated liver cirrhosis, 5–7 or a single type of complication such as SBP, 8 HRS, 9 HE, 10,11 ascites, 12,13 infections, 14 or hyponatremia 15 . A review by Bai et al examined in 2022 the efficacy of human albumin infusion in cirrhotic patients, but it did not differentiate by comparators, in the main analysis it assessed all types of indications together and analysed only a few outcomes 16 …”
Section: Introductionmentioning
confidence: 99%